Teaching the Library Research Process - Kuhlthau, Carol Collier (Rowman & Littlefield Publishers, 1994)
This practical resource gives academic librarians and school media specialists a complete instructional program for introducing students to the process of library research. The program has been tested and proven as an exceptionally effective method for guiding students in independent learning using library resources. The second edition of this highly regarded text incorporates use of newer library technologies into innovative process strategies, instructional plans, and coaching techniques. Seven basic steps of the research process are identified and described. Ready-to-use activities with worksheets are provided to help students achieve the specific task to be accomplished at each stage. In many ways the book is more timely than when the first edition was published in 1985. The library research process approach to learning integrates subject area content with essential information processing skills, preparing students to address real problems in real-world contexts in the information age. Cloth edition previously published in 1994. Paperback edition available April 2002.